Predictors of Clinical and Endoscopic Findings in Differentiating Crohn's Disease from Intestinal Tuberculosis - Li, Xuefeng; Liu, Xiaowei; Zou, Yiyou; Ouyang, Chunhui; Wu, Xiaoping; Zhou, Minghuan; Chen, Linlin; Ye, Lingjuan; Lu, Fanggen (Digestive diseases and sciences, 2011)
Background There are many similarities and overlaps in clinical manifestations and ileocolonoscopic features between Crohn's disease (CD) and intestinal tuberculosis (ITB). Differentiation between CD and ITB is of great importance. Aim To investigate the values of clinical and endoscopic findings in differential diagnosis between CD and ITB. Methods Clinical and endoscopic features of a cohort of 130 cases of CD and 122 cases of ITB from June 2003 to February 2009 were retrospectively reviewed following predetermined criteria. Parameters were screened by logistic regression analysis. Furthermore, the diagnostic efficacy of screened parameters was analyzed by regression equation (mathematical model) and receiver operating characteristic curve (ROC curve). Results The clinical features helpful in differentiating CD from ITB are hematochezia, intestinal surgery, perianal diseases, pulmonary tuberculosis, ascites, and positive of PPD skin test; the sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of regression mathematical model established by clinical features were 90.3, 76.8, 83.8, 80.7, and 88.0%, respectively. The endoscopic features helpful in differentiating CD from ITB were rectum involved lesions, longitudinal ulcer, cobblestone appearance, fixed-open ileocecal valve, transverse ulcer, and rodent ulcer; the sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of regression mathematical model established by endoscopic features were 82.9, 82.0, 82.5, 82.9, and 82.0%, respectively. Conclusions It was proposed that a diagnostic algorithm based on available clinical and endoscopic regression equation could improve the current sensitivity, specificity, and accuracy in differentiating between CD from ITB.